Assessing swells in La Réunion Island from terrestrial seismic observations, oceanographic records and offshore wave models. Issue 3 (13th March 2020) - Rindraharisaona, E J; Cordier, E; Barruol, G; Fontaine, F R; Singh, M
SUMMARY: La Réunion Island in the southwest Indian Ocean is seasonally affected by austral swells among which some extreme events may have strong impacts on coastal infrastructures. The very limited number of sensors available on and around the island and in the whole SW Indian Ocean impedes any direct monitoring of the swell activity. In this study, we analyse direct observations of the ocean swell by combining terrestrial measurements of the microseismic noise with in situ oceanographic observations issued from two pressure gauges and an Acoustic Doppler Current Profiler (ADCP), together with swell numerical modelling. The reliability of the terrestrial seismic station to characterize the ocean activity in both the primary and secondary microseisms peaks (PM and SM, respectively), and also in the long period secondary microseismic peak (LPSM) for the case of La Réunion Island is presented and discussed here. By computing the hourly RMS of the PM and LP(SM) amplitudes, we establish a transfer function between the PM and (LP)SM amplitude and the maximum wave height, which appears to be valid for any PM and LPSM amplitudes >0.15 μm and >1.0 μm, respectively. The correlation coefficient between the PM amplitude and the wave height is >0.92. It suggests that the PM amplitude can be used as a robust proxy for the swell height and may help calibrating the wave heights from other independent observable. For some swell events, we observe LPSM that correlate well (>0.91) with the local wave height suggesting a generation by coastal swell reflection. From polarization and spectral analyses, directions and periods of swells are also well retrieved from seismic data. Finally, continuous measure of the SM amplitude shows that it can be used as precursor information for distant swells that may hit La Réunion Island a few days after their generation in the southern Indian Ocean.